A biodegradable medical composite magnesium alloy rod and its preparation method and application
By stacking magnesium-zinc alloy and high-purity magnesium hollow rods on the outer surface of the magnesium-zinc alloy rod, and preparing a composite magnesium alloy rod with gradient zinc content through extrusion molding process, the problems of excessively fast degradation rate and insufficient mechanical properties of magnesium alloy rods in the prior art are solved, and the effects of early high strength and later rapid degradation are achieved.
Patent Information
- Application Number
- CN202411983533.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The corrosion degradation rate of existing medically degradable composite magnesium alloy rods is too fast in the body, which is difficult to meet the needs of bone repair. At the same time, the mechanical properties of high-purity magnesium rods cannot meet the high requirements for use strength.
By stacking magnesium-zinc alloy hollow rods and high-purity magnesium hollow rods on the outer surface of the magnesium-zinc alloy rods in turn, a composite rod with gradient zinc content is formed, and a biodegradable medical composite magnesium alloy rod is prepared through an extrusion molding process.
The composite magnesium alloy rod has high mechanical properties and degradation rate in the early stage, and is rapidly degraded and dissolved in the body in the later stage, and has good biocompatibility and ladder-type degradation performance.
Smart Images

Figure CN119770743A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomaterials, and in particular to a biodegradable medical composite magnesium alloy rod and a preparation method and application thereof. Background Art
[0002] In the field of medical bone repair, medical degradable composite magnesium alloy rods have been favored by many researchers and have become a material that can be used in the future. As a rod profile, medical degradable composite magnesium alloy rods are very suitable for rod-shaped implants such as bone nails.
[0003] Magnesium is one of the trace elements necessary for the human body. After magnesium corrodes in the human body, its products will not cause harm to the human body, meeting the biocompatibility characteristics required by biomaterials. Moreover, the density of magnesium is similar to that of human bone. Implanting it into the human body as a repair material can effectively stimulate bone growth and healing. Adding some zinc to magnesium alloys can increase the degradation rate of magnesium alloys. However, if high-zinc magnesium alloys such as Mg-6Zn are directly used as medical bone repair materials, the corrosion and degradation rate in the body is relatively fast, which is difficult to meet the actual bone repair needs. The mechanical properties of high-purity magnesium rods cannot meet the higher strength requirements for use, and cannot be well supported in the early stage. Therefore, there is an urgent need for a composite magnesium alloy rod that can not only meet the early strength requirements, but also quickly degrade itself in the later stage, so as to meet the needs of good bone repair. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a biodegradable medical composite magnesium alloy rod and its preparation method and application. The preparation method provided by the present invention is simple to operate, and the obtained biodegradable medical composite magnesium alloy rod can not only meet the early strength requirements, but also can be rapidly degraded in the later stage.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a biodegradable medical composite magnesium alloy rod, which is characterized by comprising the following steps:
[0007] A first magnesium-zinc alloy hollow rod, a second magnesium-zinc alloy hollow rod, ... an nth magnesium-zinc alloy hollow rod, and a high-purity magnesium hollow rod are sequentially stacked on the outer surface of the magnesium-zinc alloy rod to obtain a combined rod, wherein n=1 to 7;
[0008] Extruding the combined rods to obtain biodegradable medical composite magnesium alloy rods;
[0009] The zinc contents of the magnesium-zinc alloy rod, the first magnesium-zinc alloy hollow rod, the second magnesium-zinc alloy hollow rod, ... the nth magnesium-zinc alloy hollow rod decrease gradually.
[0010] Preferably, the ratio of the diameter of the magnesium-zinc alloy rod to the thickness of the first magnesium-zinc alloy hollow rod, the second magnesium-zinc alloy hollow rod...the nth magnesium-zinc alloy hollow rod is 1-4:1-4:...:1-4;
[0011] The diameter of the combined rod is 30-60 mm.
[0012] Preferably, the zinc content of the Mg-Zn alloy rod, the first Mg-Zn alloy hollow rod, the second Mg-Zn alloy hollow rod, ... the nth Mg-Zn alloy hollow rod decreases gradually within the range of 6.5 to 0.5 wt %.
[0013] Preferably, the zinc content of the magnesium-zinc alloy rod is 3.5-6.5wt%; and the zinc content of the nth magnesium-zinc alloy hollow rod is 0.5-3.5wt%.
[0014] Preferably, the temperature for extrusion molding of the rod is 300-500°C.
[0015] Preferably, the extrusion ratio of the rod extrusion molding is 1:4-50.
[0016] Preferably, the rod extrusion molding is performed 1 to 3 times.
[0017] The present invention provides a biodegradable medical composite magnesium alloy rod prepared by the above preparation method, wherein the zinc content of the biodegradable medical composite magnesium alloy rod decreases gradually from the center to the outer layer.
[0018] Preferably, the diameter of the biodegradable medical composite magnesium alloy rod is 2 to 10 mm.
[0019] The present invention provides application of the biodegradable medical composite magnesium alloy rod in the preparation of medical implant materials.
[0020] The invention provides a method for preparing a biodegradable medical composite magnesium alloy rod, comprising the following steps: stacking a first magnesium-zinc alloy hollow rod, a second magnesium-zinc alloy hollow rod, ... an nth magnesium-zinc alloy hollow rod, and a high-purity magnesium hollow rod in sequence on the outer surface of a magnesium-zinc alloy rod to obtain a combined rod, wherein n=1-7; performing rod extrusion molding on the combined rod to obtain a biodegradable medical composite magnesium alloy rod; the zinc content of the magnesium-zinc alloy rod, the first magnesium-zinc alloy hollow rod, the second magnesium-zinc alloy hollow rod, ... the nth magnesium-zinc alloy hollow rod is gradually reduced. The present invention processes a laminated composite rod of high-purity magnesium and magnesium-zinc alloy, and the longitudinal section of the obtained composite magnesium alloy rod is a high-purity magnesium layer, a low-zinc magnesium alloy layer, a high-zinc alloy layer, a low-zinc magnesium alloy layer, and a high-purity magnesium layer. Due to the differences in the plastic deformation mechanism and dynamic recrystallization mechanism of each alloy, and the different concentrations of zinc elements contained in its composition from the inside to the outside, the microstructure and performance of the composite magnesium alloy rod are significantly different from the inside to the outside. The rod has a low corrosion degradation rate in the early stage, and can be rapidly degraded and dissolved in the body in the later stage, and has good biocompatibility and comprehensive mechanical properties, as well as ladder-type degradation performance. The mechanical properties of the medical composite magnesium alloy rod prepared by the present invention are better than those of the high-purity magnesium substrate. In the early stage of degradation, the excellent microdegradability of the substrate pure magnesium can be maintained to maintain the mechanical support requirements of the implantable material. In the later stage, the degradation of the material will be accelerated due to the gradual increase in the zinc content.
[0021] The present invention adopts an extrusion molding method, which can simply and quickly obtain a composite magnesium alloy rod, has low cost, a wide range of applications, and high promotion value. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The schematic diagram of the structure of the biodegradable medical composite magnesium alloy rod;
[0023] Figure 2 This is a cross-sectional metallographic image of the medical composite magnesium alloy rod obtained in Example 1;
[0024] Figure 3 The Vickers hardness data of the cross section of the medical composite magnesium alloy rod obtained in Example 1;
[0025] Figure 4 This is a cross-sectional metallographic image of the medical composite magnesium alloy rod obtained in Example 2;
[0026] Figure 5 The Vickers hardness data of the cross section of the medical composite magnesium alloy rod obtained in Example 2;
[0027] Figure 6 The mechanical properties of the medical composite magnesium alloy rod obtained in Example 1 are compared with those of Comparative Examples 1 to 4;
[0028] Figure 7 The mechanical properties of the medical composite magnesium alloy rod obtained in Example 2 are compared with those of Comparative Examples 1 to 3;
[0029] Figure 8 It is a comparison chart of the weight loss rate of the medical composite magnesium alloy rods obtained in Examples 1 and 2 and Comparative Examples 1 to 4. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing a biodegradable medical composite magnesium alloy rod, comprising the following steps:
[0031] A first magnesium-zinc alloy hollow rod, a second magnesium-zinc alloy hollow rod, ... an nth magnesium-zinc alloy hollow rod, and a high-purity magnesium hollow rod are sequentially stacked on the outer surface of the magnesium-zinc alloy rod to obtain a combined rod, wherein n=1 to 7;
[0032] Extruding the combined rods to obtain biodegradable medical composite magnesium alloy rods;
[0033] The zinc contents of the magnesium-zinc alloy rod, the first magnesium-zinc alloy hollow rod, the second magnesium-zinc alloy hollow rod, ... the nth magnesium-zinc alloy hollow rod decrease gradually.
[0034] The present invention stacks a first magnesium-zinc alloy hollow rod, a second magnesium-zinc alloy hollow rod, ... an nth magnesium-zinc alloy hollow rod, and a high-purity magnesium hollow rod on the outer surface of a magnesium-zinc alloy rod in sequence to obtain a combined rod. In the present invention, the inner diameter of the first magnesium-zinc alloy hollow rod is ≥ the diameter of the magnesium-zinc alloy rod, the inner diameter of the second magnesium-zinc alloy hollow rod is ≥ the outer diameter of the first magnesium-zinc alloy hollow rod, ... the inner diameter of the nth magnesium-zinc alloy hollow rod is ≥ the outer diameter of the n-1th magnesium-zinc alloy hollow rod, and the inner diameter of the high-purity magnesium hollow rod is ≥ the outer diameter of the nth magnesium-zinc alloy hollow rod.
[0035] In the present invention, n=1-7, preferably 3-5; as a specific embodiment of the present invention, n=1, 2, 3, 4, 5, 6 or 7.
[0036] In the present invention, when n=1, the present invention sequentially stacks a magnesium-zinc alloy hollow rod and a high-purity magnesium hollow rod on the outer surface of the magnesium-zinc alloy rod to obtain a combined rod; when n=2, the present invention sequentially stacks a first magnesium-zinc alloy hollow rod, a second magnesium-zinc alloy hollow rod and a high-purity magnesium hollow rod on the outer surface of the magnesium-zinc alloy rod.
[0037] In the present invention, the ratio of the diameter of the magnesium-zinc alloy rod to the thickness of the first magnesium-zinc alloy hollow rod, the second magnesium-zinc alloy hollow rod...the nth magnesium-zinc alloy hollow rod is preferably 1-4:1-4:...:1-4. In the present invention, the diameter of the magnesium-zinc alloy rod is preferably 5-10 mm. In the present invention, the thickness of the first magnesium-zinc alloy hollow rod, the second magnesium-zinc alloy hollow rod...the nth magnesium-zinc alloy hollow rod is preferably 5-10 mm, more preferably 6-8 mm. In the present invention, the thickness of the high-purity magnesium hollow rod is preferably 5-10 mm, more preferably 6-8 mm.
[0038] In the present invention, the diameter of the combined rod is preferably 30-60 mm. As a specific embodiment of the present invention, the diameter of the combined rod is 30 mm, 40 mm, 50 mm or 60 mm.
[0039] In the present invention, the zinc content of the Mg-Zn alloy rod, the first Mg-Zn alloy hollow rod, the second Mg-Zn alloy hollow rod, ... the nth Mg-Zn alloy hollow rod is reduced in a gradient, preferably in a gradient range of 6.5 to 0.5 wt%. In the present invention, the zinc content of the Mg-Zn alloy rod is preferably 3.5 to 6.5 wt%, more preferably 4 to 6 wt%, and the remainder is magnesium. In the present invention, the zinc content of the nth Mg-Zn alloy hollow rod is preferably 0.5 to 3.5 wt%, more preferably 1 to 2.5 wt%, and the remainder is magnesium. As a specific embodiment of the present invention, when n=2, the zinc content of the Mg-Zn alloy rod, the first Mg-Zn alloy hollow rod, and the second Mg-Zn alloy hollow rod is preferably 6 wt%, 4 wt%, and 2 wt%, respectively. When n=1, the zinc content of the Mg-Zn alloy rod and the first Mg-Zn alloy hollow rod is preferably 4 wt% and 2 wt%, respectively.
[0040] In the present invention, the purity of the high-purity magnesium hollow rod is preferably 99.98%.
[0041] Before the stacking, the present invention preferably pre-treats the magnesium-zinc alloy rod, the first magnesium-zinc alloy hollow rod, the second magnesium-zinc alloy hollow rod...the nth magnesium-zinc alloy hollow rod and the high-purity magnesium hollow rod, and the pre-treatment includes grinding, polishing, cleaning and drying performed in sequence.
[0042] The present invention performs rod extrusion molding on the combined rod to obtain a biodegradable medical composite magnesium alloy rod. In the present invention, the temperature of the rod extrusion molding is preferably 300-500°C. As a specific embodiment of the present invention, the temperature of the rod extrusion molding is 300°C, 350°C, 400°C, 450°C or 500°C.
[0043] In the present invention, the extrusion ratio of the rod extrusion molding is preferably 1:4-50, more preferably 1:5-40; as a specific embodiment of the present invention, the extrusion ratio is 1:4, 1:5, 1:10, 1:20, 1:23.8, 1:25, 1:30, 1:40 or 1:50.
[0044] In the present invention, the number of extrusions for the rod extrusion molding is preferably 1 to 3 times; as a specific embodiment of the present invention, the number of extrusions is 1 time, 2 times or 3 times.
[0045] The present invention provides a biodegradable medical composite magnesium alloy rod prepared by the above-mentioned preparation method, wherein the zinc content of the biodegradable medical composite magnesium alloy rod decreases gradually from the center to the outer layer. In the present invention, the biodegradable medical composite magnesium alloy rod comprises a high zinc-magnesium alloy layer, a low zinc-magnesium alloy layer and a high-purity magnesium layer from the inside to the outside. In the present invention, the zinc content of the magnesium-zinc alloy material of the low zinc-magnesium alloy layer is preferably 0.5-3.5wt%, more preferably 1-2.5wt%, and the balance is magnesium; the zinc content of the magnesium-zinc alloy material of the high zinc-magnesium alloy layer is preferably 3.5-6.5wt%, more preferably 4-6wt%, and the balance is magnesium.
[0046] In the present invention, the diameter of the biodegradable medical composite magnesium alloy rod is preferably 2 to 10 mm. As a specific embodiment of the present invention, the diameter of the biodegradable medical composite magnesium alloy rod is 2 mm, 4 mm, 6 mm, 8 mm, or 10 mm.
[0047] As a specific embodiment of the present invention, the structural schematic diagram of the biodegradable medical composite magnesium alloy rod is as follows Figure 1 As shown, Figure 1 Among them, 1 is the first high zinc-magnesium alloy layer, 2 is the second high zinc-magnesium alloy layer, 3 is the low zinc-magnesium zinc alloy layer, and 4 is the high-purity magnesium layer; wherein the zinc content of the first high zinc-magnesium alloy layer is higher than that of the second high zinc-magnesium alloy layer.
[0048] The present invention provides the use of the above biodegradable medical composite magnesium alloy rod in the preparation of medical implant materials. In the present invention, the medical implant material is preferably a bone repair material, and more preferably a bone nail.
[0049] The biodegradable medical composite magnesium alloy rod provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0050] Example 1
[0051] Prepare a φ40*5mm high-purity magnesium hollow rod (purity of 99.98%), a φ30*5mm magnesium-zinc alloy hollow rod with a zinc content of 2wt%, a φ20*5mm magnesium-zinc alloy hollow rod with a zinc content of 4wt%, and a φ10mm magnesium-zinc alloy rod with a zinc content of 6wt%. The above rods are ground, polished, cleaned and dried for pretreatment. The above rods are stacked and extruded at 450°C with an extrusion ratio of 23.8 to obtain a biodegradable medical composite magnesium alloy rod extruded into φ8.2mm.
[0052] Figure 2 This is a cross-sectional metallographic image of the medical composite magnesium alloy rod obtained in Example 1. From the figure, it can be seen that the organization is clearly layered, with a total of 7 layers, and the fusion is good. From the outside to the inside, the high-purity magnesium layer is about 50μm, the low-zinc-magnesium alloy layer is about 1500μm, and the high-zinc-magnesium alloy layer is about 5000μm. The grain size decreases from the outside to the inside.
[0053] Figure 3 The Vickers hardness data of the cross section of the medical composite magnesium alloy rod obtained in Example 1. It can be seen from the figure that on the alloy layers with different structures, the hardness data increases as the rod moves toward the center, then increases and then decreases, indicating that the concentration of zinc element in the rod increases from the outside to the center.
[0054] Example 2
[0055] Prepare a φ40*10mm high-purity magnesium hollow rod (purity of 99.98%), a φ20*6mm magnesium-zinc alloy hollow rod with a zinc content of 2wt%, and a φ8mm magnesium-zinc alloy rod with a zinc content of 4wt%. The above rods are ground, polished, cleaned and dried for pre-treatment. The above rods are stacked and extruded at 420°C with an extrusion ratio of 23.8 to obtain a biodegradable medical composite magnesium alloy rod extruded into φ8.2mm.
[0056] Figure 4 This is a cross-sectional metallographic image of the medical composite magnesium alloy rod obtained in Example 2. From the image, it can be seen that the organization is clearly stratified, with a total of 5 layers, and the fusion is good. From the outside to the inside, the high-purity magnesium layer is about 1800μm, the low-zinc-magnesium alloy layer is about 1500μm, and the high-zinc-magnesium alloy layer is about 1600μm. The grain size decreases from the outside to the inside.
[0057] Figure 5 The Vickers hardness data of the cross section of the medical composite magnesium alloy rod obtained in Example 2. It can be seen from the figure that on the alloy layers with different structures, the hardness data increases as the rod moves toward the center, then increases and then decreases, indicating that the concentration of zinc element in the rod increases from the outside to the center.
[0058] Comparative Example 1
[0059] A φ40 mm high-purity magnesium rod (denoted as Z0) with a zinc content of 0 was pre-treated by grinding, polishing, cleaning and drying, and then extruded at 400°C with an extrusion ratio of 23.8 to obtain a φ8.2 mm medical biodegradable pure magnesium rod.
[0060] Comparative Example 2
[0061] A φ40 mm low zinc magnesium alloy bar (denoted as Z2) with a zinc content of 2 wt% was subjected to grinding, polishing, cleaning and drying pretreatment, and then extruded at 400° C. with an extrusion ratio of 23.8 to obtain a φ8.2 mm medical biodegradable magnesium alloy bar.
[0062] Comparative Example 3
[0063] A φ40 mm high zinc magnesium alloy bar (denoted as Z4) with a zinc content of 4 wt% was subjected to grinding, polishing, cleaning and drying pretreatment, and then extruded at 400° C. with an extrusion ratio of 23.8 to obtain a φ8.2 mm medical biodegradable magnesium alloy bar.
[0064] Comparative Example 4
[0065] A φ40 mm high zinc magnesium alloy bar (denoted as Z6) with a zinc content of 6 wt% was subjected to grinding, polishing, cleaning and drying pretreatment, and then extruded at 400° C. with an extrusion ratio of 23.8 to obtain a φ8.2 mm medical biodegradable magnesium alloy bar.
[0066] Performance Testing
[0067] (1) Figure 6 The mechanical properties of the medical composite magnesium alloy rod obtained in Example 1 are compared with those of Comparative Examples 1 to 4. The test standard of the mechanical properties refers to the circular proportional specimen model R08 of GB / T 16865-2023 "Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products".
[0068] It can be seen that the strength of the medical composite magnesium alloy rod is much higher than the high-purity magnesium rod of Comparative Example 1 after extrusion, and the strength is slightly lower than that of the Z2 rod, but the plasticity is better than that of the Z2 rod and the Z4 rod, and slightly lower than that of the Z6 rod.
[0069] Figure 7 The mechanical properties of the medical composite magnesium alloy rod obtained in Example 2 are compared with those of Comparative Examples 1 to 3. It can be seen that the strength of the medical composite magnesium alloy rod is much higher than the high-purity magnesium rod of Comparative Example 1 after extrusion, and the strength is slightly lower than that of the Z2 rod, although the plasticity is poor.
[0070] (2) The samples of the embodiment and the comparative example were cut into 10 mm long rods and immersed in 200 ml PBS for 1 week, 2 weeks and 4 weeks for in vitro degradation experiments. Figure 8 This is a comparison chart of the weight loss rates of the composite rods obtained in Examples 1 and 2 and Comparative Examples 1 to 4. From the figure, it can be seen that the degradation rates of the rods in Examples 1 and 2 are close to that of high-purity magnesium at 1 week and 2 weeks, while in Example 1 at 4 weeks is much greater than high-purity magnesium and Z2, while Example 2 is close to high-purity magnesium and Z2, indicating that the degradation rates of the rods in the examples are different due to the thickness of the high-purity magnesium layer on the outer layer of the rod. The greater the thickness, the slower the degradation rate in the later stage.
[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a biodegradable medical composite magnesium alloy rod, characterized in that: The following steps are involved: A first magnesium-zinc alloy hollow rod, a second magnesium-zinc alloy hollow rod, ... an nth magnesium-zinc alloy hollow rod, and a high-purity magnesium hollow rod are sequentially stacked on the outer surface of the magnesium-zinc alloy rod to obtain a combined rod, wherein n=1 to 7; Extruding the combined rods to obtain biodegradable medical composite magnesium alloy rods; The zinc contents of the magnesium-zinc alloy rod, the first magnesium-zinc alloy hollow rod, the second magnesium-zinc alloy hollow rod, ... the nth magnesium-zinc alloy hollow rod decrease gradually.
2. The preparation method according to claim 1, characterized in that: The ratio of the diameter of the magnesium-zinc alloy rod to the thickness of the first magnesium-zinc alloy hollow rod, the second magnesium-zinc alloy hollow rod, ... the nth magnesium-zinc alloy hollow rod is 1-4:1-4:...:1-4; The diameter of the combined rod is 30-60 mm.
3. The preparation method according to claim 1, characterized in that: The zinc content of the magnesium-zinc alloy rod, the first magnesium-zinc alloy hollow rod, the second magnesium-zinc alloy hollow rod ... the nth magnesium-zinc alloy hollow rod is gradually reduced within the range of 6.5 to 0.5 wt%.
4. The preparation method according to claim 1 or 3, characterized in that: The zinc content of the magnesium-zinc alloy rod is 3.5-6.5wt%; the zinc content of the nth magnesium-zinc alloy hollow rod is 0.5-3.5wt%.
5. The preparation method according to claim 1, characterized in that: The temperature of the rod extrusion molding is 300-500°C.
6. The preparation method according to claim 1 or 5, characterized in that: The extrusion ratio of the rod extrusion molding is 1:4-50.
7. The preparation method according to claim 1, characterized in that: The extrusion times of the rod extrusion molding are 1 to 3 times.
8. The biodegradable medical composite magnesium alloy rod prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The zinc content of the biodegradable medical composite magnesium alloy rod decreases gradually from the center to the outer layer.
9. The biodegradable medical composite magnesium alloy rod according to claim 8, characterized in that: The diameter of the biodegradable medical composite magnesium alloy rod is 2 to 10 mm.
10. Use of the biodegradable medical composite magnesium alloy rod according to claim 8 or 9 in the preparation of medical implant materials.